2016
DOI: 10.1002/jcla.21976
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Molecule Levels in Type 2 Diabetes Mellitus

Abstract: In our study, KIM-1 levels were significantly different suggesting that urinary KIM-1 levels may be an early marker in patients with diabetic nephropathy. J. Clin. Lab. Anal. 00:1-6, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…Although our diabetic subject had different average age, duration of disease, race and socioeconomic status, the result had high consistency with other studies and also demonstrated that NGAL and KIM-1 appeared earlier in nephropathy. 15,16,27,28,31,[35][36][37][38][39] Sensitivity and specificity of urine NGAL and KIM-1 in early diagnostic diabetic nephropathy of our study were similar to other researches. 39,40 Kapoula et al had showed the pooled sensitivity and specificity among the different settings analyzed ranged from 0.42 (95% CI, 0.22-0.66) to 1.00 (95% CI, 0.99-1.00) and 0.72 (95% CI, 0.62-0.80) to 0.98 (95% CI, 0.50-1.00) in T2DM patients, respectively.…”
Section: Dovepresssupporting
confidence: 90%
“…Although our diabetic subject had different average age, duration of disease, race and socioeconomic status, the result had high consistency with other studies and also demonstrated that NGAL and KIM-1 appeared earlier in nephropathy. 15,16,27,28,31,[35][36][37][38][39] Sensitivity and specificity of urine NGAL and KIM-1 in early diagnostic diabetic nephropathy of our study were similar to other researches. 39,40 Kapoula et al had showed the pooled sensitivity and specificity among the different settings analyzed ranged from 0.42 (95% CI, 0.22-0.66) to 1.00 (95% CI, 0.99-1.00) and 0.72 (95% CI, 0.62-0.80) to 0.98 (95% CI, 0.50-1.00) in T2DM patients, respectively.…”
Section: Dovepresssupporting
confidence: 90%
“…In previous studies on diabetic nephropathy, the relationship between albuminuria and uKIM-1 was not obvious. A weak positive correlation between ACR and uKIM-1 was found, but KIM-1 was increased even in patients with moderate albuminuria [13,25,26]. There is no evidence that in diabetic nephropathy albumin is toxic to proximal tubule cells.…”
Section: Discussionmentioning
confidence: 82%
“…A positive correlation exists between KIM-1 and MA as well as microalbumin/Creatinine ratio. [30] MA patients have significantly higher BP and duration of diabetes compared to normolabumin uric subjects. HDL-c was significantly lower in MA subjects while FPG, TGs, TC and VLDL-C were found to be marginally higher in microalbuminuric than normolabumin uric.…”
Section: Microalbuminuriamentioning
confidence: 84%